Impact of a Heterozygous C1RR301P/WT Mutation on Collagen Metabolism and Inflammatory Response in Human Gingival Fibroblasts - Chengjuan Qu; Cecilia Koskinen Holm (Cells)
Periodontal Ehlers–Danlos syndrome arising from heterozygous pathogenic mutation in C1R and/or C1S genes is an autosomal-dominant disorder characterized by early-onset periodontitis. Due to the difficulties in obtaining and culturing the patient-derived gingival fibroblasts, we established a model system by introducing a heterozygous C1RR301P/WT mutation into human TERT-immortalized gingival fibroblasts (hGFBs) to investigate its specific effects on collagen metabolism and inflammatory responses. A heterozygous C1RR301P/WT mutation was introduced into hGFBs using engineered prime editing. The functional consequences of this mutation were assessed at cellular, molecular, and enzymatic levels using a variety of techniques, including cell growth analysis, collagen deposition quantification, immunocytochemistry, enzyme-linked immunosorbent assay, and quantitative real-time reverse transcription polymerase chain reaction. The C1RR301P/WT-mutated hGFBs (mhGFBs) exhibited normal morphology and growth rate compared to wild-type hGFBs. However, mhGFBs displayed upregulated procollagen α1(V), MMP-1, and IL-6 mRNA expression while simultaneously downregulating collagen deposition and C1r protein levels. A modest accumulation of unfolded collagens was observed in mhGFBs. The mhGFBs exhibited a heightened inflammatory response, with a more pronounced increase in MMP-1 and IL-6 mRNA expression compared to TNF-α/IL-1β-stimulated hGFBs. Unlike cytokine-stimulated hGFBs, cytokine-stimulated mhGFB did not increase C1R, C1S, procollagen α1(III), and procollagen α1(V) mRNA expression. Our results suggest that the C1RR301P/WT mutation specifically disrupts collagen metabolism and inflammatory pathways in hGFBs, highlighting the mutation’s role in these processes. While other cellular functions appear largely unaffected, these findings underscore the potential of targeting collagen metabolism and inflammation for therapeutic interventions in pEDS.